2020
DOI: 10.3389/fncel.2019.00584
|View full text |Cite
|
Sign up to set email alerts
|

rTMS Regulates the Balance Between Proliferation and Apoptosis of Spinal Cord Derived Neural Stem/Progenitor Cells

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive technique that uses electromagnetic fields to stimulate the brain. rTMS can restore an impaired central nervous system and promote proliferation of neural stem/progenitor cells (NSPCs), but optimal stimulus parameters and mechanisms underlying these effects remain elusive. The purpose of this study is to investigate the effect of different rTMS stimulus parameters on proliferation and apoptosis of spinal cord-derived NSPCs, the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For induction of cell differentiation, we followed the Gibco Neurobiology Protocol Handbook, as previously described [ 10 ]. sp-NSPCs were allowed to adhere to cover slips coated with poly- l -lysine (0.01%, P4707, Sigma) and laminin (10 μg/mL, L2020, Sigma) in NSPC growth medium for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…For induction of cell differentiation, we followed the Gibco Neurobiology Protocol Handbook, as previously described [ 10 ]. sp-NSPCs were allowed to adhere to cover slips coated with poly- l -lysine (0.01%, P4707, Sigma) and laminin (10 μg/mL, L2020, Sigma) in NSPC growth medium for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…For such purposes, many studies focus on the mechanism of rTMS acting on the neural stem cells (NSCs) and neural precursor cells (NPCs), which are related to neurogenesis, and astrocytes or microglia connected with neuroinflammation ( Hong et al, 2020 ). For instance, rTMS has therapeutic effects on depression because it can reverse the decrease of NSCs and enhance neurogenesis, and rTMS could regulate the balance between proliferation and apoptosis of NSCs ( Zhao et al, 2019 ). For neuroprotective effect, it has been reported that rTMS could improve functional recovery by inhibiting neurotoxic polarization of astrocytes in ischemic rats, which means rTMS may regulate inflammation through the action of neural glial cells ( Sasso et al, 2016 ; Cullen et al, 2019 ; Clarke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%